Urban Environment Management as Instrument to Increase Local Ability and Human Resources - Triono Edy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Entering the XXI century (or millennium III), the future development on the one hand to show the city as an important role player and unexpected and never experienced before in the history of anywhere. On the other side of town facing more diverse development problems for many developing countries may not be handled alone. The development of the world also headed to the nature of democratic governance and increasing the amount of local autonomy. This means that the ability of areas, including human resources must he increased to be ahle to respond to changes and new possibilities. All efforts should still be made within the framework of sustainable development principles (city) sustained due to the quality of the environment in general is very bad, in some places almost critical. In this paper, in addition to the problem of instruments for efforts to increase local capacity and human resources, a variety of definitions, scope and paradigm shift will be discussed also. Key words: Urban, environment management, local abilities, human resources I. INTRODUCTION There is one side that is associated with the environmental management aspects of the city that is the pressure greater demographic.